1991
DOI: 10.1037/0882-7974.6.3.467
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depressive disorders in adult children caring for demented parents.

Abstract: Current and lifetime rates of disorders outlined in the Diagnostic and Statistical Manual of Mental Disorders (3rd ed., rev., DSM-III-R) were compared in 78 adult children caring for a parent with a progressive dementia and 78 control subjects. The frequencies of depressive and anxiety disorders did not differ between groups in the years prior to caregiving, and there were no differences between groups in first-degree relatives' incidence of psychiatric disorder. During the years they had been providing care, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
2
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(116 citation statements)
references
References 24 publications
6
105
2
3
Order By: Relevance
“…For example, Dura and colleagues report that dementia caregivers are significantly more likely to have a depressive disorder compared to demographically matched non-caregivers (14). In a later study, children caregivers of parents with dementia were found to be significantly more likely to have depressive and anxiety disorder relative to non-caregivers (15). Russo and colleagues also report caregivers to have greater prevalence of psychiatric disorders than demographically matched non-caregivers (16).…”
Section: Objectivementioning
confidence: 90%
“…For example, Dura and colleagues report that dementia caregivers are significantly more likely to have a depressive disorder compared to demographically matched non-caregivers (14). In a later study, children caregivers of parents with dementia were found to be significantly more likely to have depressive and anxiety disorder relative to non-caregivers (15). Russo and colleagues also report caregivers to have greater prevalence of psychiatric disorders than demographically matched non-caregivers (16).…”
Section: Objectivementioning
confidence: 90%
“…"Wife" caregivers seem to be pushed by a stronger sense of duty and are inclined to care more scrupulously for their husband, but at the same time, they would like to desert this role; all this contributes to a growing sense of guilt and uneasiness. Gonzales-Salvador et al [16] and Waite et al [17] found no impact whatsoever of familial relationship on caregivers' stress levels; -living arrangement: living with the patient is highlighted by most studies as a risk factor for caregiver suffering [4, 11,18], though not all reach the same conclusion [19,20];…”
Section: Introductionmentioning
confidence: 99%
“…In the context of anxiety, between 3.7% and 76.5% of caregivers present symptoms of anxiety [18] and between 10.0% and 16.0% sufer from an anxiety disorder [8,24]. The severity of physical health consequences of the person with dementia and the caregiver's overload and their coping style (escape-avoidance and confrontation, especially) are factors associated with higher levels of anxiety [18].…”
Section: Dementiamentioning
confidence: 99%
“…The impact of caregiving on the emotional state of caregivers is well documented [7]. Speciically, it has been found that 10.0% of caregivers have anxiety disorders [8] and between 8.9% and 32.0% have a major depressive episode [9,10], being insomnia or hypersomnia, diminished ability to think or concentrate and depressed mood the most frequent symptoms (see Table 1) [10].…”
Section: Introductionmentioning
confidence: 99%